Bioactive bacterial cellulose sulfate electrospun nanofibers for tissue engineering applications. (18th May 2018) - Palaninathan, Vivekanandan; Raveendran, Sreejith; Rochani, Ankit K.; Chauhan, Neha; Sakamoto, Yasushi; Ukai, Tomofumi; Maekawa, Toru; Kumar, D. Sakthi
Abstract: Cellulosic materials have been of tremendous importance to mankind since its discovery due to its superior properties and its abundance in nature. Recently, an increase in demand for alternate green materials has rekindled the interest for cellulosic materials. Here, bacterial cellulose has been functionalized with sulfate groups through acetosulfation to gain solubility in aqueous media, which provides access to several applications. The cell viability, antioxidant, and hemocompatibility assays have verified the biocompatible and antioxidant characteristics of bacterial cellulose sulfate (BCS) in both in vitro and ex vivo conditions. Further, novel BCS/polyvinyl alcohol nanofibers were fabricated by simple electrospinning route to engineer ultrafine nanoscale fibers. The biological evaluation of BCS/polyvinyl alcohol nanofiber scaffolds was done using L929 mouse fibroblast cells, which confirmed that these nanofibers are excellent matrices for cell adhesion and proliferation.